Rehabilitation studies for individuals with alcohol and substance use disorders: systematic review - Akkurt Yalçıntürk, Aydan; Dikeç, Gül; Ata, Elvan Emine (Journal of Dependence, 2019)
The aim of this systematic review is to review the rehabilitation studies of alcohol and substance use disorders in the last decade. In this study, experimental studies published in PubMed and Turkish Psychiatric Index databases between 2008 and 2018 were searched. Thirteen experimental studies on alcohol and substance use disorders in PubMed (12) and Turkish Psychiatric Index (1). Eye Movement Desensitization and Reprocessing (EMDR), Biofeedback Therapy (2), Probation Dependence Program, Pet Therapy, Tai Chi, Lyric Analysis, Music Therapy, Motivational Interviewing, 28 Day Inpatient Rehabilitation Program, Smoking Cessation Treatment (2) and Episodic Future Thinking. Rehabilitation studies increased the individuals’ readiness to quit substance, social skills, quality of life, positive future perception, stay abstinence, attendance to self-help programs after treatment and get professional help and improve their physical health. Rehabilitation studies for individuals with alcohol and substance use disorders are limited, and cost effective, continuous easy applied rehabilitation programs are needed and they could prevent relapses among these population.